PARTISIPASI ORANG TUA DALAM PENYELENGGARAAN PEMBELAJARAN DARING MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS VII DI SMP NEGERI 1 KEPANJEN - Farih Tsabitah Imtinan; Mohammad Afifulloh; Adi Sudrajat (VICRATINA, 2021)
Online learning will not be realized without the participation of parents as guardians of the students. The purpose of this study was to describe the readiness of parents in dealing with the implementation of online learning for Islamic Religious Education subjects, the forms of parental participation and the supporting and inhibiting factors for parental participation in the implementation of online learning for Islamic Religious Education subjects. This research uses a qualitative approach with the type of case study research. Data collection techniques was in the form of observation, interviews and documentation. The subjects of this study were the principal, PAI teacher and 4 parents of class VII A students. The results showed that: (1) The readiness of the parents in terms of mental and facilities was seen in a ready condition; (2) The forms of parental participation include providing motivation, providing guidance and giving attention; (3) The factors behind the emergence of parental participation were parental occupation and income, education, parents' busyness, parental awareness, parents who are technologically stuttering, family structure, and children's characteristics. Kata Kunci: Partisipasi Orang Tua, Pembelajaran Daring, Pendidikan Agama Islam